Estudo da dependência das propriedades de recobrimento com métodos de Química Computacional: análise dos diferentes tipos de funcionais da densidade - Monteiro, Shirlene de Albuquerque (2023)
One of the main objectives of quantum chemistry is to investigate qualitatively and quantitatively the chemical interactions of elements in molecules to explain the nature of chemical bonds, since empirically these phenomena are difficult to be observed. With the advancement of computational chemistry, it was possible to verify the behavior of the most diverse systems and types of bonds making use of chemical bond analysis methods, such as the Quantum Theory of Atoms in Molecules (QTAIM) which provides information on chemical bonds from a topological mapping of the distribution of electronic density and which is widely used for comparative purposes. The coating model (OP) uses localized molecular orbitals (LMOs) to analyze chemical bonding, calculating coating properties and generating electron density maps. All these properties are calculated using the Chemical Bond Overlap Software (ChemBOS) computer program (MOURA et al., 2020). Both methods are being used in this research. The objective of this work was to evaluate the efficiency of the chemical bond covering method comparing the results with the methods of electronic structures Hartree-Fock (HF) and the density functional theory (DFT). Initially, systems consisting of the single covalent bonds of interest (C-C), (C-F) and (C-O) were used, respectively, ethane (H3C-CH3), fluoromethane (H3C-F) and methanol (H3C–OH), using the functionals according to the Jacobi ladder, including SVWN (LDA), BLYP (GGA), B3LYP (GGAH), M06-L (mGGA), M06 (mGGA), M06-2X (mGGA), M06-HF (mGGA) , B97-2 (HGGA), B97 (HGGA), B97-X (HGGA) and B97X-D (HGGA) with the base function def2TZVP in all calculations, being able to verify the best performances among them. The functionals B97 (HGGA), B97X (HGGA) and B97X-D (HGGA) showed less variability in obtaining the OP chemical binding descriptors, while the QTAIM descriptors were more dependent for the mechanisms B3LYP (GGAH), M06-L (mGGA), M06 (mGGA), M06-2X (mGGA).